Determination of Trace Amounts of Cationic Surfactant Cetyl Trimethyl Ammonium Bromide by Liquid-Liquid Extraction-Spectrophotometry Method. - AFSHAR, Z.GH.; PARHAM, H. (Asian Journal of Chemistry, 2010)
This study describes a simple, sensitive and selective extractionspectrophotometric method for the determination of trace amounts of cationic surfactant of cetyl trimethyl ammonium bromide (CTAB), an anti-dandruff is reporting. The CTAB-orange II ion-pair in bufferic media is quantitatively extracted into chloroform and its absorbance is measured at 487 nm at room temperature. The effect of different variables such as solvent, volume of extracting solvent, volume of anionic reagent, pH, ionic strength (NaCl 0.1 M) and shaking time is investigated and optimum conditions for quantitative extraction of CTAB is obtained. Linear calibration graph over the CTAB concentration range 0.5-9.0 μg mL-1 and regression coefficient of 0.9999 is obtained. The relative standard deviation of eight replicate determinations of 5 μg mL-1 of CTAB is 1.519 %. Limit of detection of the method is 0.012 μg mL-1. The interfering effect of a large number of diverse ions on the determination CTAB was studied. The method is used for determination of CTAB in the anti-dandruff shampoo and good results are obtained.